2020
DOI: 10.1186/s13075-020-02286-w
|View full text |Cite
|
Sign up to set email alerts
|

AST/ALT ratio as a predictor of mortality and exacerbations of PM/DM-ILD in 1 year—a retrospective cohort study with 522 cases

Abstract: Objective To assess the associations between aspartate transaminase/alanine transaminase ratio (DRR) and mortality in patients with polymyositis/dermatomyositis-associated interstitial lung disease (PM/DM-ILD). Patients and methods This was a retrospective cohort study, which included 522 patients with PM/DM-ILD whose DRR on admission were tested at West China Hospital of Sichuan University during the period from January 1, 2008, to December 31, 2018. Cox regression models were used to estimate hazard ratios… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Li et al discovered that a higher AST/ALT ratio was an independent predictor of 1‐year mortality in polymyositis‐/dermatomyositis‐associated interstitial lung disease. 23 Likewise, a greater AST‐to‐ALT ratio at baseline was correlated with subsequent all‐cause mortality, especially cardiovascular diseases. 21 , 24 Cancer survival‐related studies have shown that a high AST/ALT ratio is associated with poor outcome of renal cell carcinoma, 13 head and neck carcinoma, 25 and oral and oropharyngeal carcinoma 26 among other cancers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Li et al discovered that a higher AST/ALT ratio was an independent predictor of 1‐year mortality in polymyositis‐/dermatomyositis‐associated interstitial lung disease. 23 Likewise, a greater AST‐to‐ALT ratio at baseline was correlated with subsequent all‐cause mortality, especially cardiovascular diseases. 21 , 24 Cancer survival‐related studies have shown that a high AST/ALT ratio is associated with poor outcome of renal cell carcinoma, 13 head and neck carcinoma, 25 and oral and oropharyngeal carcinoma 26 among other cancers.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, several studies demonstrated the association of the AST‐to‐ALT ratio with mortality. Li et al discovered that a higher AST/ALT ratio was an independent predictor of 1‐year mortality in polymyositis‐/dermatomyositis‐associated interstitial lung disease 23 . Likewise, a greater AST‐to‐ALT ratio at baseline was correlated with subsequent all‐cause mortality, especially cardiovascular diseases 21,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Put another way, a failure or inability to raise ALT as the disease progressed portended a worse outcome. Importantly, low ALT levels have been well-established as markers of frailty, especially in the elderly, and have been significantly associated with long-term mortality as well as worse short-term outcomes among a wide range of hospitalized patients [ 22 26 ]. Ours is the first cohort to suggest that this adverse prognostic value of low ALT may extend to hospitalized COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have shown that serum CRP, ferritin, IL-18, and LDH levels are related to DM-ILD, confirming this view ( 3 , 29 ). During ILD progression, macrophage activation can promote hepatocyte injury, resulting in increased ALT and AST levels ( 31 ). Previous data also showed that serum CEA and CA125 levels were closely related to DM-ILD ( 32 ).…”
Section: Discussionmentioning
confidence: 99%